Mass customization information systems in business - Blecker, Thorsten; Friedrich, Gerhard 1961- (Information Science Reference, 2007)
"This book describes original, innovative works on IT systems for mass customization, and provides a multitude of solutions, tools, concepts and successful realizations of IT systems for mass customization. It discusses state-of-the-art mass customization while depicting the importance of IT in making the strategy function efficiently in order to support the business processes required for manufacturing individualized products" - Provided by publisher
Includes bibliographical references and index
Keywords: Administración de productos; Flexibele productiesystemen; Klantgerichtheid; Preferencias de los consumidores; Productiemanagement; Relaciones con los clientes; Sistemas flexibles de manufactura; Flexible manufacturing systems; Product management; Customer relations; Consumers' preferences; Mass Customization; Produktmanagement; Informationssystem; Aufsatzsammlung